Size-dependent adhesion energy of shape-selected Pd and Pt nanoparticles. Issue 22 (24th May 2016) - Ahmadi, M.; Behafarid, F.; Cuenya, B. Roldan
Abstract : Shape-selected Pd and Pt nanoparticles (NPs) synthesized via inverse micelle encapsulation and supported on TiO2 (110) were used as model systems to investigate the role of the NP size on the NP/support adhesion energy. Abstract : Thermodynamically stable shape-selected Pt and Pd nanoparticles (NPs) were synthesized via inverse micelle encapsulation and a subsequent thermal treatment in vacuum above 1000 °C. The majority of the Pd NPs imaged via scanning tunneling microscopy (STM) had a truncated octahedron shape with (111) top and interfacial facets, while the Pt NPs were found to adopt a variety of shapes. For NPs of identical shape for both material systems, the NP-support adhesion energy calculated based on STM data was found to be size-dependent, with large NPs ( e.g. ∼6 nm) having lower adhesion energies than smaller NPs ( e.g. ∼1 nm). This phenomenon was rationalized based on support-induced strain that for larger NPs favors the formation of lattice dislocations at the interface rather than a lattice distortion that may propagate through the smaller NPs. In addition, identically prepared Pt NPs of the same shape were found to display a lower adhesion energy compared to Pd NPs. While in both cases, a transition from a lattice distortion to interface dislocations is expected to occur with increasing NP size, the higher elastic energy in Pt leads to a lower transition size, which in turn lowers the adhesion energy of Pt NPs compared to Pd.